2017
DOI: 10.4081/aiua.2017.4.296
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, multicenter, controlled study, comparing efficacy and safety of a new complementary and alternative medicine (CAM) versus Solifenacin Succinate in women with overactive bladder syndrome

Abstract: the small number of patients does not permit definitive conclusions; however, the results of the research showed the greater effectiveness and tolerability of CAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…52 Recent trials using P. cuspidatum have not reported significant toxicity. 53,54 In this current study, clinically used antibiotics for treating Bartonella-associated infections, including AZI and DOX, showed weak activity in eradicating stationary phase B. henselae cells (Table 1, Figure 1, and Figure 2). This finding coincides with the reported discrepancies in antibiotic efficacies between in vitro MIC data and clinical data from patients.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…52 Recent trials using P. cuspidatum have not reported significant toxicity. 53,54 In this current study, clinically used antibiotics for treating Bartonella-associated infections, including AZI and DOX, showed weak activity in eradicating stationary phase B. henselae cells (Table 1, Figure 1, and Figure 2). This finding coincides with the reported discrepancies in antibiotic efficacies between in vitro MIC data and clinical data from patients.…”
Section: Discussionmentioning
confidence: 71%
“…A study investigating the mechanism of action of P. cuspidatum using a network pharmacology approach suggested that the component polydatin might play a pivotal role in the therapeutic effects of P. cuspidatum 52 . Recent trials using P. cuspidatum have not reported significant toxicity 53,54 …”
Section: Discussionmentioning
confidence: 99%
“…18 In a multicenter randomized controlled trial, Vecchioli-Scaldazza et al. 19 have compared Kubiker with Solifenacin Succinate in women with OAB, demonstrating the effectiveness and good tolerability profile of this CAM.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, patients with OAB are usually proposed to follow anti-muscarinic therapies, which are often discontinued because of adverse effects, poor efficacy, or drug costs. 18 In a multicenter randomized controlled trial, Vecchioli-Scaldazza et al 19 have compared Kubiker with Solifenacin Succinate in women with OAB, demonstrating the effectiveness and good tolerability profile of this CAM.…”
Section: Discussionmentioning
confidence: 99%
“…A study unraveling the mechanism of action of Polygonum cuspidatum using a network pharmacology approach, suggested that polydatin might play a pivotal role in the therapeutic effects of Polygonum cuspidatum [98]. Recent trials using Polygonum cuspidatum have not reported significant toxicity [99, 100]. One of the active constituents, resveratrol, has been shown to be rapidly absorbed [101], well-tolerated [102] and associated with minimal toxicity except mild diarrhea at an oral dose of 2000mg 2x/day for 2 weeks [103].…”
Section: Discussionmentioning
confidence: 99%